Psychosis After Switch in Opioid Maintenance Agonist and Risperidone-Induced Pisa Syndrome: Two Critical Incidents in Dual Diagnosis Treatment. Issue 2 (3rd April 2017) - Sutter, Manuel; Walter, Marc; Dürsteler, Kenneth M.; Strasser, Johannes; Vogel, Marc
ABSTRACT: Background and aims : Dual diagnosis commonly occurs among patients with an opioid use disorder. Treatment is ideally performed in an integrated fashion. We present a case that illustrates the complex and challenging psychiatric and medical therapy of such patients in the light of the literature.Case description : We report on a 56-year-old patient with schizophrenia and opioid dependence who experienced both risperidone-induced Pisa syndrome and, 3 years later, acute psychosis after switching the opioid substitution medication from methadone to slow-release oral morphine due to QT prolongation.Conclusions : With the current availability of a diversity of substitution opioids in Switzerland (methadone, buprenorphine, diacetylmorphine, sustained-release oral morphine), studies on differential effectiveness of these agents in opioid-dependent subpopulations with selective comorbidity profiles are desirable. The same is true for further investigation of the involvement of the opioid receptor system in schizophrenia. In clinical practice, any alteration of opioid medication in patients with dual diagnosis and a history of schizophrenia should be accompanied by close observation for psychotic symptoms.